2017
DOI: 10.1371/journal.pone.0177307
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the use practitioner-based complementary and alternative medicine over time in Canada: Cohort and period effects

Abstract: BackgroundThe use of complementary and alternative medicine (CAM) is growing. However the factors contributing to changes over time and to birth cohort differences in CAM use are not well understood.SettingWe used data from 10186 participants, who were aged 20–69 years at the first cycle of data collection in the longitudinal component of the Canadian National Population Health Survey (1994/95-2010/11). We examined chiropractic and other practitioner-based CAM use with a focus on five birth cohorts: pre-World … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 56 publications
(62 reference statements)
3
18
0
3
Order By: Relevance
“…Kanadalaisessa tutkimuksessa hyödynnettiin väestötason terveyskyselyä, joka mahdollisti 16 vuoden seurantatutkimuksen. Siinä todettiin CAM-hoitojen käytön lisääntyneen 5% yli kymmeneen prosenttiin vuosien 1994-1995 ja 2010-2011 välillä (32) Tutkiessamme uskoa CAM-hoitojen parantavuuteen muodostimme summamuuttujan kysymyksestä "Ovatko seuraavat hoidot/keinot mielestänne sellaisia, joilla voidaan parantaa jokin sairaus tai sairauksia?" (Kyllä/Ei) valitsemalla siihen CAM-hoitoja kuvaavat osiot.…”
Section: Cam-hoitojen Käytön Tutkimusunclassified
“…Kanadalaisessa tutkimuksessa hyödynnettiin väestötason terveyskyselyä, joka mahdollisti 16 vuoden seurantatutkimuksen. Siinä todettiin CAM-hoitojen käytön lisääntyneen 5% yli kymmeneen prosenttiin vuosien 1994-1995 ja 2010-2011 välillä (32) Tutkiessamme uskoa CAM-hoitojen parantavuuteen muodostimme summamuuttujan kysymyksestä "Ovatko seuraavat hoidot/keinot mielestänne sellaisia, joilla voidaan parantaa jokin sairaus tai sairauksia?" (Kyllä/Ei) valitsemalla siihen CAM-hoitoja kuvaavat osiot.…”
Section: Cam-hoitojen Käytön Tutkimusunclassified
“…9 This change is consistent with data, largely from North America, suggesting recent substantial increases in CM use in the community as a whole. 12,13 Nutritional supplements were the most common CM in the FDS2 cohort, with omega-3 fatty acids or fish oil being taken by almost a quarter of participants using CM. Based on conservative estimates, the median annual cost of CM in FDS2 participants using them was just over $100, but some Complementary medicine use in diabetes participants were spending thousands of dollars on CM each year.…”
Section: Discussionmentioning
confidence: 99%
“…9 There is evidence that CM use has since increased in the general population in developed countries. 12,13 In addition, there have also been significant changes in conventional pharmacotherapies used by patients for type 2 diabetes and its comorbidities, 14 in tandem with a recent reduction in rates of complications 15 that may influence the decision to use CM. We have, therefore, evaluated baseline CM use and its associates in participants in Phase II of the FDS (FDS2) conducted between 2008 and 2011.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with similar studies, as most patients use CAM together with their prescribed conventional therapy and not in place of, which is also known as integrative medicine. 2,21,22 However, about one-fourth of participants reported using CAM because they were not satisfied with their conventional medical therapy, or lack thereof. Studies have shown that patients may use CAM because they gradually lose confidence or satisfaction in conventional care for chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated increased CAM use in females, adults, and those with higher education when compared to CAM Non-users. 11,21,22 Comparisons between CAM Users and CAM Non-users were not performed due to our limited sample size, therefore making the study underpowered to adequately analyze these comparisons. These comparisons are warranted in future studies.…”
Section: Discussionmentioning
confidence: 99%